Integration and Language Learning of Newly Arrived Migrants Using Mobile Technology. Issue 1 (5th April 2017) - Bradley, Linda; Lindström, Nataliya Berbyuk; Hashemi, Sylvana Sofkova
The purpose of this study is to investigate the mobile activities newly arrived migrants are engaged in when learning the Swedish language and about Swedish culture and society. Further, the study also explores the use of a mobile application (app) provided to the newly arrived migrants to use for pronunciation practice. The study involved 38 newly arrived Arabic speaking migrants participating in an introduction program of the Swedish language and Swedish culture provided by the Swedish government. The participants were divided into two groups: a control group who received training according to the traditional introduction programme and an experimental group who used a mobile app for pronunciation training as a complement to the programme. We applied a combination of qualitative and quantitative methods for data collection and analysis. The participants were interviewed about their use of mobile phones as well as recorded in a number of activities inside and outside the classroom to compare their language evolvement. In addition, surveys, logging of weekly mobile activities and observations were performed. The results show that the participants used a wide range of different mobile tools, both inside and outside the classroom. However, they used the mobiles mostly for communication with their family and friends rather than for communication with Swedes and learning Swedish. Further, compared to the control group, the experimental group showed an improved speech tempo and self-confidence in speaking. The study thus indicates that focused linguistic training with a pronunciation app is useful for developing spoken language skills, which can lead to improved integration. The participants expressed need and interest in having more mobile apps for both language and culture training.